The Analysis of Permeability and Mechanical Properties of Sand Moulding Using Mixed Material Clamshell (Placuna placenta) on Sand Casting - Kritchakhris Nawettanaprasert; Zakaria Bagus Aminanta; Putut Murdanto (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
This study objected to determine mechanical properties of sand moulding by conducting tensile test, compressive and shear test, and also permeability test. This study also had the other objective that was analyse clamshell (Placuna placenta) as mixture material for bentonite as binder in manufacturing sand moulding in order to reduce the usage of bentonite. The method that used in this study was pre-experimental method with One-Shot Case Study model. The best mechanical properties obtained on sample 3 clamshell 11%, permeability results obtained was 190 ml/min, tensile strength results obtained for the dry sand was 0.015 kg/cm2, compressive strength obtained for the dry sand was 2.91 kg/cm2, and the shear strength of sand moulding in dry condition was 0.92 kg/cm2.